Wildlife & natural resource management - Deal, Kevin H. 4 0 16; 5 (Albany, N.Y. : Delmar Publishers, 1998)
A textbook which surveys the field of wildlife management and describes the various types of animals, birds, reptiles, amphibians, and fish that must be preserved.
Includes index.
Keywords: 2 -- 0; 6; Wildlife management;Wildlife management. -- 20 -- Juvenile literature; 20; 2